Recursive fury: Conspiracist ideation in the blogosphere in response to research on conspiracist ideation - Lewandowsky, Stephan; Cook, John; Oberauer, Klaus; Marriott, Michael (Frontiers in Psychology)
This article, first published by Frontiers on 18 March 2013, has been the subject of complaints. Given the nature of some of these complaints, Frontiers has provisionally removed the link to the article while these issues are investigated, which is being done as swiftly as possible and which Frontiers management considers the most responsible course of action. The article has not been retracted or withdrawn. Further information will be provided as soon as possible. Thank you for your patience.